Pemanfaatan AI dalam Pembelajaran Berbasis TI di SMA Negeri 1 Onan Runggu Kecamatan Onan Runggu Kabupaten Samosir - Sorang Pakpahan; Harianja, Andy Paul; Sitorus, Lamhot (ULEAD : Jurnal E-Pengabdian, 2025)
This study explores the utilization of Artificial Intelligence (AI) in technology-based learning at SMA Negeri 1 Onan Runggu, located in Samosir Regency. The integration of AI into the educational process aims to enhance learning effectiveness, personalize student experiences, and support teachers in managing instructional materials. Using a qualitative-descriptive method, data were collected through interviews, observations, and documentation involving teachers and students. The findings indicate that AI-based tools, such as intelligent tutoring systems, educational chatbots, and automated assessments, have begun to be applied in classroom and digital learning settings. Although challenges remain—such as limited infrastructure and the need for teacher training—the implementation of AI shows promising results in increasing student engagement and supporting independent learning. This study highlights the importance of adopting AI-driven approaches to meet the demands of modern education and improve the overall quality of learning in schools.